Perkembangan Gonad dan Musim Pemijahan Kerang Sepetang (Pharella acutidens) di Ekosistem Mangrove Dumai, Riau - Efriyeldi .; Dietriech G Bengen; Ridwan Affandi (Maspari Journal : Marine Science Research, 2012)
ABSTRACTThisÂ researchÂ aimsÂ toÂ studyÂ theÂ gonadalÂ developmentÂ andÂ spawningÂ seasonofÂ â€œsepetangâ€Â clamÂ (PharellaÂ acutidens).TheÂ studyÂ wasÂ carriedÂ outÂ Â overÂ 12Â monthÂ periodÂ fromÂ NovemberÂ 2010Â toÂ OctoberÂ 2011Â atÂ Â DumaiÂ mangroveÂ ecosystem.â€œSepetangâ€Â clamÂ samplesÂ wereÂ obtainedÂ fromÂ theÂ DumaiÂ mangroveÂ ecosystemÂ monthlyÂ atÂ threeÂ station.Â TheÂ clamÂ collectedÂ fromÂ plotÂ 1Â xÂ 1Â m2onÂ quadratÂ Â transect.Â ReproductiveÂ aspectsÂ suchÂ asÂ sexÂ ratio,Â gonadalÂ development,gonadosomaticÂ indexÂ (GSI),Â andÂ oocytesÂ diameterÂ wereÂ studied.TheÂ resultÂ showedÂ thatÂ â€œsepetangâ€Â clamÂ canÂ beÂ sexedÂ atÂ theÂ sizeÂ moreÂ thanÂ 35Â mm.Â NoÂ specimensÂ hermaphroditismÂ wasÂ observed.Â TheÂ maleÂ toÂ femaleÂ ratioÂ wasÂ Â 1Â :Â 1.12.Â HistologicalÂ analysisÂ indicatedÂ thatÂ P.Â acutidenshadfourÂ distinguishableÂ gonadÂ developmentÂ inÂ maleÂ andÂ femaleÂ clam,Â namelyÂ earlyÂ active,Â lateÂ active,Â ripeÂ andÂ partiallyÂ spawned.Â MeanÂ Â oocyteÂ diameterÂ didÂ notÂ showedÂ patternÂ monthly,Â exceptÂ onMayÂ toÂ July,Â meanÂ oocyteÂ diameterÂ small.Â BasedÂ onÂ gonadalÂ development,Â GSIÂ andÂ meanÂ oocytesÂ diameter,Â â€œsepetangâ€Â clamÂ spawningÂ continuedÂ throughoutÂ theÂ yearÂ Â Â andÂ Â peakÂ spawningÂ seasonÂ myÂ beÂ onÂ May-July.Â KeywordsÂ :Â â€œsepetangâ€Â clam,Â histological,Â sexÂ ratio,Â gonadosomaticÂ indexÂ ABSTRAKPenelitianÂ yangÂ bertujuanÂ mengkajiÂ perkembanganÂ gonadÂ danÂ musimÂ pemijahanÂ kerangÂ sepetangÂ (P.Â acutidens)Â telahÂ dilakukanÂ selamaÂ 12Â bulan,Â mulaiÂ bulanÂ NovemberÂ 2010Â sampaiÂ OktoberÂ 2011Â diÂ ekosistemÂ mangroveÂ Dumai.Â Â KerangÂ sepetangÂ diperolehÂ dariÂ ekosistemÂ Â mangroveÂ DumaiÂ BaratÂ padaÂ tigaÂ stasiunÂ setiapÂ bulan.Â KerangÂ dikumpulkanÂ dariÂ plotÂ 1Â xÂ 1Â m2Â padaÂ transekÂ kuadrat.Â PadaÂ penelitianÂ iniÂ dikajiÂ nisbahÂ kelamin,Â tahapÂ perkembanganÂ gonad,Â indeksÂ kematanganÂ gonad,Â Â danÂ diameterÂ oosit.Â HasilÂ penelitianÂ menunjukkanÂ bahwaÂ kerangÂ sepetangÂ bersifatÂ dioecious.Â EmpatÂ tahapanÂ kematanganÂ gonadÂ ditemukanÂ padaÂ penelitianÂ ini,Â meliputiÂ aktifÂ awal,Â aktifÂ akhir,Â matangÂ danÂ dikeluarkanÂ sebagian.Â Rata-rataÂ diameterÂ oositÂ tidakÂ menunjukkanÂ adanyaÂ polaÂ setiapÂ bulan,Â namunÂ padaÂ bulanÂ Mei-JuliÂ diameterÂ oositÂ lebihÂ kecil.Â BerdasarkanÂ tahapÂ perkembanganÂ gonad,Â indeksÂ kematanganÂ gonad,Â danÂ diameterÂ oositÂ kerangÂ sepetangÂ memijahÂ sepanjangÂ tahunÂ danÂ puncakÂ pemijahanÂ padaÂ bulanÂ Mei.KataÂ KunciÂ :Â kerangÂ sepetang,Â histologi,Â nisbahÂ kelamin,Â indeksÂ kematanganÂ gonad